Outcome of children with rhinovirus detection prior to allogeneic hematopoietic cell transplant - Mowrer, Clayton (Pediatr Transplant, 2018)
Rhinoviruses are commonly detected in symptomatic and asymptomatic children prior to HCT. Unlike pre‐HCT detection of other respiratory viruses, it is not known whether RV detection, with or without clinical symptoms, is associated with worse outcomes in children post‐HCT. In a retrospective study of children undergoing allogeneic HCT from January 2009 to February 2015, 91 children underwent allogeneic HCT, and 62 children had RPP testing within 30 days pre‐HCT. Fifty‐six (90%) children had either no pathogen (n = 34, 55%) or single RV detection (n = 22, 35%), which was the most common pathogen identified. Compared with virus negative children, children with pre‐HCT RV detection were not more likely to require ventilated support and did not have longer length of stay, higher mortality, or less days alive and out of the hospital within the first 100 days post‐HCT. In a secondary analysis of all 56 patients with RPP testing and no pathogen or RV alone detected, the seven children with LRTI had less days alive and out of the hospital within the first 100 days post‐HCT compared with the 49 children who were either asymptomatic or had URTI (10 vs 60 days, P = 0.002). In a bootstrapped regression model, presence of LRTI, not RV detection, was significantly associated with decreased days alive and out of the hospital within the first 100 days post‐HCT. Thus, pre‐HCT detection of RV, without associated LRTI, does not always warrant HCT delay.